(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ano-rectal problems are progressively enhancing at an alarming pace in the society and Arsha is the commonest among all the prevailing ano-rectal disorders. Arsha in modern parlance can be compared with Hemorrhoids. Hemorrhoids are varicosity of the plexus of rectal veins lying under mucosa. Aim: This study is an attempt to evaluate the efficacy of Kutaja (Holarrhena antidysenterica) Pratisaarneya Kshara in the management of Internal Hemorrhoids. Methodology: A total of 30 patients having signs and symptoms of Internal hemorrhoids were selected for Kutaja Pratisaarneya Kshara application till the Pakwa Jambu Phala stage was achieved and Kshara application was repeated after 7 days if the mass has not regressed completely. Result: This study revealed that 83.33% of patients got cured, 16.67% of patients showed marked improvement. Conclusion: Kutaja has Stambhana properties, so it showed a great result in per rectal bleeding. Moreover, regression of Hemorrhoidal mass was due to Vilayana, Shoshana and Lekhana properties of Kutaja.